Ancestral knowledge the midwives of traditional medicine, immemorial learnings that are still preserved - Córdoba-Villota, Elvira Eugenia; Velasquez-Mantilla, Daniel Andrés (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
The present work focuses on analyzing the behavior of science on studies of traditional medical practices focused on midwifery that currently retain different ethnic groups. A review of scientific articles was carried out in the databases Scopus, WOS and ScienceDirect, Ebsco, ProQuest, Redalyc, Scielo, DialNet between 2017 and 2022. At present, midwifery is a practice of cultural resistance that is waiting to be rescued and taken into account within Western medical learning techniques.